FUNCTIONAL MODELLING APPROACH IN THE DESIGN OF AN ELECTRICAL SHOE DRYER - Sudin, Mohd. Nizam; Ramli, Faiz Redza; Tan, CheeFai (Suranaree Journal of Science and Technology Office, Suranaree University of Technology, 2013)
Functional basis is a design language consisting of a set of functions and a set of flows that are used to form a sub-function. This paper presents the application of functional basis to develop a functional model during the conceptual design of an electrical shoe dryer. In this research, reconciled functional basis was employed to develop the functional model of the electrical shoe dryer. Later on, the means to achieve the required sub-functions are identified based on the designer’s experience. In the embodiment design stage the identified means of the required functions are arranged to form the final layout of the electrical shoe dryer. In conclusion, the application of functional basis in the development of an electrical shoe